1x-9=7/8x+1

Simple and best practice solution for 1x-9=7/8x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x-9=7/8x+1 equation:



1x-9=7/8x+1
We move all terms to the left:
1x-9-(7/8x+1)=0
Domain of the equation: 8x+1)!=0
x∈R
We add all the numbers together, and all the variables
x-(7/8x+1)-9=0
We get rid of parentheses
x-7/8x-1-9=0
We multiply all the terms by the denominator
x*8x-1*8x-9*8x-7=0
Wy multiply elements
8x^2-8x-72x-7=0
We add all the numbers together, and all the variables
8x^2-80x-7=0
a = 8; b = -80; c = -7;
Δ = b2-4ac
Δ = -802-4·8·(-7)
Δ = 6624
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{6624}=\sqrt{144*46}=\sqrt{144}*\sqrt{46}=12\sqrt{46}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-80)-12\sqrt{46}}{2*8}=\frac{80-12\sqrt{46}}{16} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-80)+12\sqrt{46}}{2*8}=\frac{80+12\sqrt{46}}{16} $

See similar equations:

| 1x-9=7/8x | | 49-7x=19+8x | | 168=8(11-5x)+80 | | -2x-9=12x+26 | | -8v+6=5(v-4) | | 3/8(x-24)+x=19 | | 4.5x+6=3.5x+5 | | 1.28=(x-2)/0.15 | | 9+2x-5=10,x= | | -x+5x=35-x | | 5x+35x-10=8(5x+9) | | 30x^2+3000=0 | | 7x+3(5-3)=5 | | 9+2x-5=10x= | | x/3.1+2=2.777 | | 12/x=27/243 | | 5/2x+1/2=13 | | 7x-2=98 | | 17x+44=17x+77 | | 1.75x+10=3.5x-16.25 | | g/9+6=2 | | -4=-2/3n+1/3 | | 2c+3=2(6+3c)+6c | | 1/2x+2=x | | n-6/6=n-2/9 | | 2/3x-21/3=17 | | 1.75x+10=3.5x | | 4x+6(4x-3)=-8 | | -c/10+26=46 | | 7(−2k+4)−6=7k−20 | | M-4n=-6 | | 2-5m=-(5m+6) |

Equations solver categories